Insurance-markets Equilibrium with Sequential Non-convex Straight-time and Over-time Labor Supply - VASILEV, Aleksander (Journal of Mathematical Economics and Finance; Vol 4 No 2 (2018): JMEF, Volume IV, Issue 2(7), Winter 2018, 2018)
This note describes the lottery - and insurance-market equilibrium in an economy with non-convex straight-time and overtime employment. In contrast to Hansen and Sargent (1988), the overtime-decision is a sequential one. This requires two separate insurance market to operate, one for straight-time work, and one for overtime. In addition, given that the labor choice for regular and overtime hours is made in succession, the insurance market for overtime needs to open once the insurance market has closed. This segmentation and sequentiality of insurance markets operation is a new result in the literature and a direct consequence of the sequential nature of the overtime labor decision.